EFFECT OF DAY OLD CHICKS WEIGHT ON PRODUCTIVE PERFORMANCE OF TWO BROILER STRAINS AND THEIR CROSSING - AL-Shamire, J. S. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This experment was conducted at the Poultry Farm،Animal production Dept./College of Agriculture. University of Baghdad from 1-4-2014 to 12-5-2014. to investigate the potential effect of day old chicks weight produced from two broiler strains and their crossing Ross 308 , Arbor Acres and Ross 308 x Arbor Acres on productive performance . A total of 360 day all chicks were distributed randomly to 6 groups with 4 replicate pens )15 birds / pens). The experimental groups were: T1= Ar-medium; T2= Ar - Large ; T3= R-medium; T4= R -Large; T5= R - Arb-medium; T6= R - Ar-Large. Results showed that body weight, weekly average gain, feed conversion ratio, dressing percentage and relative breast weight in female were significantly (p<0.05) better in group T3 and T5 compared to heavy chicks . While there was no significant differences between sex or strain for breast relative weight and other cuts. It could be concluded from this study that chicks with medium weight gave better or equal live weight compared to heaver strain .however crossing between hybrids improved productive performance of broilers .